Infantile-onset Pompe disease complicated by sickle cell anemia: Case report and management considerations - Starosta, Rodrigo Tzovenos; Hou, Ying-Chen Claire; Leestma, Katelyn; Singh, Prapti; Viehl, Luke; Manwaring, Linda; Granadillo, Jorge Luis; Schroeder, Molly C.; Colombo, Jamie N.; Whitehead, Halana; Dickson, Patricia Irene; Hulbert, Monica L.; et al. (Frontiers in Pediatrics, 2022)
Infantile-onset Pompe disease (IOPD) is a rare, severe disorder of lysosomal storage of glycogen that leads to progressive cardiac and skeletal myopathy. IOPD is a fatal disease in childhood unless treated with enzyme replacement therapy (ERT) from an early age. Sickle cell anemia (SCA) is a relatively common hemoglobinopathy caused by a specific variant in the hemoblogin beta-chain. Here we report a case of a male newborn of African ancestry diagnosed and treated for IOPD and SCA. Molecular testing confirmed two GAA variants, NM_000152.5: c.842G>C, p.(Arg281Pro) and NM_000152.5: c.2560C>T, p.(Arg854*) in trans, and homozygosity for the HBB variant causative of SCA, consistent with his diagnosis. An acute neonatal presentation of hypotonia and dilated cardiomyopathy required ERT with alglucosidase alfa infusions preceded by immune tolerance induction (ITI), as well as chronic red blood cell transfusions and penicillin V potassium prophylaxis for treatment of IOPD and SCA. Clinical course was further complicated by multiple respiratory infections. We review the current guidelines and interventions taken to optimize his care and the pitfalls of those guidelines when treating patients with concomitant conditions. This report emphasizes the importance of newborn screening, early intervention, and treatment considerations for this complex patient presentation of IOPD and SCA.